Analisis Peran Moderasi Locus Of Control Pada Pengaruh Tekanan Kerja Dan Kepuasan Kerja Terhadap Komitmen Organisasional - Agung Wibowo (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2011)
Abstract The organizational commitment have become serious problem, therefore require to investigating what factors becoming its cause so that can be solved effectively. The purpose of this study was to empirically examine the influence of the job stress and job satisfaction on organizational commitment with the locus of control moderation. The populations of the research were auditors working at public accountant firms in Jakarta. This research use purposive sampling method to collect data. A sample of 58 auditors was employed to investigate the influence of the job satisfaction and job stress on organizational commitment with the locus of control moderation. The result of this research indicates that there is a positive effect of the job satisfaction and job stress on organizational commitment. Keywords : Job Stress, Job Satisfaction, Organizational Commitment, Locus of Control.